Impact of brief psychological intervention on reducing the psychological symptoms after COVID-19 infection among healthcare workers (HCWs) in Nepal (Journal of Psychiatrists' Association of Nepal, 2023)
Background: Studies from various countries showed that HCWs suffered from psychological problems during the period of COVID-19 and  psychosocial intervention to address the issues was found effective. This study aimed to find out the status of depression, anxiety, stress and post-traumatic stress disorder (PTSD) symptoms among HCWs after COVID-19 infection including determining the outcome of a brief psychosocial intervention protocol in reducing the symptoms.Methods: Group-based pretest-posttest interventional design was adopted. A total of 380 HCWs, recovered from the COVID-19 infections were selected through a purposive sampling technique. The study period was from November 2020 to January 2021. The Nepalese-translated and validated version of the Depression, Anxiety and Stress Scale – 21(DASS-21) and Impact of Event Scale-Revised (IES-R) were used to assess the symptoms. A brief psychosocial intervention was done by a trained clinical psychologist and compared the differences in mean scores on the level of depression, anxiety, stress and PTSD symptoms before and after the intervention.Results: This study found that about 11% HCWs had symptoms of depression, 31% had symptoms of anxiety, 3% had stress and 98.50% had symptoms of PTSD. The paired sample t-test showed a significant difference between the means for the IES-R before the intervention (M=47.94, SD=14.53) and after the intervention (M=43.63, SD=15.35); t = 5.003 and p=.000 as well as the DASS-21 mean score before (M=14.11, SD=11.74) and after (M=12.28, SD=10.81); t = 2.97 and p = .003 the intervention.Conclusion: This study showed that this intervention protocol was found effective in reducing the symptoms of depression, anxiety, stress and PTSD symptoms of the participants. However, a longitudinal study is needed to confirm these findings